Effect of parturition and recombination bovine somatotropin (rBST) on the metabolic profile of dairy cows - J.M. Estrada; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1990)
Summary Blood samples were collected from 16 Holstein cows around parturition to obtain baseline values of various hormones and metabolites. At 90 ± 3 days postcalving, cows were divided into two groups (8 cows/group) and injected with either saline (control) or 25 mg rBST/d for 28 consecutive days. Blood was sampled on days 0, 1, 5, 10, 15, 30, and 45 after the beginning of treatment and analyzed for insulin, glucagon, growth hormone, glucose, and blood urea nitrogen (BUN). Milk production and composition were recorded as well as body weights and condition scores. Cows receiving rBST had higher milk yields than control cows during the treatment period. Milk lactose percentage also increased for cows on rBST, but other milk components remained unchanged. Plasma insulin decreased, and glucagon, growth hormone, glucose, and BUN increased from 10 days prepartum to 10 days postpartum. During the treatment period, insulin and glucagon decreased slightly for the rBST group, growth hormone increased for both rBST and control groups, and glucose and BUN were similar between rBST and control groups. Body weights and body condition scores decreased after parturition but remained unchanged during the injection period.; Dairy Day, 1990, Kansas State University, Manhattan, KS, 1990; The 1990 Annual KSU Dairy Day is known as Dairy Day, 1990
Keywords: Dairy Day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-148-S; Report of progress (Kansas Agricultural Experiment Station); 608; Dairy; Parturition and recombination; Somatotropin (rBST); Metabolic profile